Smart Manufacturing Using Artificial Intelligence and its Impact on Developing Lean Marketing Strategies - Sultan, Zainab Tuama; Alkhazraje, Mohammed Edan; Muhsin, Esraa Ali (International Review of Management and Marketing, 2026)
With the rapid digital transformation and adoption of technologies such as artificial intelligence, the Internet of Things, and big data analysis in manufacturing processes, it has become necessary to develop marketing strategies that rely on flexibility and high efficiency. This research focuses on employing smart manufacturing to improve the marketing decision-making process, reduce waste, and increase the ability to adapt to market variables. This research aims to explore the relationship between smart manufacturing and lean marketing strategies and how integrating these two fields can enhance the competitiveness of industrial enterprises. The Baghdad Sewing Factory (Al-Khaym Factory) was chosen as the site for implementing the research. The descriptive analytical approach was used and a purposive sample of managers and officials in the factory departments was selected, specifically those related to the production and manufacturing departments. (79) responses were collected. The data were analyzed using SPSS V.26S. The research concluded that smart manufacturing affects the development of lean marketing strategies and that the combination of smart manufacturing and lean marketing contributes to improving the operational and marketing performance of the manufacturing institution.